Transformation of suburbs of Saint-Petersburg in post-Soviet period - Maria Podkorytova (European Regional Science Association (ERSA), 2014)
The collapse of Soviet Union caused the emergency of completely new conditions in city development. Big cities faced many challenges during the transformation and every part of the city space was involved into the process. Saint-Petersburg was deeply involved into the process of transformation and as provided by the theory of innovation diffusion in absolute majority of cases the transformation was spreading from the core to the suburbs. But for an every suburb this process was quite special. The transformation of suburbs of the city and their further development were determined by the range of conditions including not only location, infrastructure and economical specialization but also historical background and some other special features in every case. Suburbs of Saint-Petersburg differ dramatically in their historical background. Applied to the process of transformation this differences bring us to the necessity of classifying the suburbs into three groups: - Group 1: founded and developed before the appearance of the Soviet Union; faced 2 transformations in their history (like Pushkin and Peterhof); - Group 2: founded and developed after the appearance of the Soviet Union; faced 1 transformation in their history (like Vsevolozhsk); - Group 3: development started after the collapse of Soviet Union and is in progress right now (like Shushary). In every group it's possible to find special development features that showed up in post-Soviet period of city development. The Saint-Petersburg city space is determined by the city core. Suburbs are mostly more connected to the city core than to one another. This tendency can be seen for example in commuting. But with the population increase various projects aimed at creating the alternative to the city center emerge. Many of them include comprehensive development of suburbia and increase of the commuting between the suburbs without entering the center (which is possible after the opening of the encircling highway). So now it becomes even more important to understand the processes that took place in the suburbia and their influence to the city space as a whole.
Keywords: 330